The Neuroprotective Potential of Betalains: A Focused Review - Cristina Ştefănescu; Oliviu Voştinaru; Cristina Mogoşan; Gianina Crişan; Georgeta Balica (Plants)
Betalains are natural, hydrophilic pigments present in a variety of plants from the order Caryophyllales, extensively used as non-toxic food colorants and antioxidants. In recent decades, betalains have been intensively researched, with numerous studies confirming their anti-inflammatory, antioxidant, antimicrobial, and antinociceptive properties. More recently, due to a significant increase in the aging population worldwide, there has been growing interest in the study of preventive effects of betalains on age-related, degenerative brain diseases. The aim of this review is to evaluate the potential neuroprotective role of betalains in the prevention of neurodegenerative diseases like Alzheimer’s disease and Parkinson’s disease, as well as other types of neurodegenerative and ischemic brain injuries. Preclinical in vivo and in vitro pharmacological studies investigating the neuroprotective effects of betalains are reviewed, with a focus on the putative mechanisms of action. Available studies in humans are also presented.